Challenge-hindrance stressors and innovative performance among dental graduate students in China: a moderated mediation model - Mao Zhao; Yating Yu; Mei Zhong; Bingpeng Lin (Humanities & Social Sciences Communications)
Abstract Improving the academic innovative performance of dental graduate students is vital for the development of dentistry. Given that dental graduate students face intense academic competition, the mechanisms of challenge and hindrance stress on innovative performance have not been thoroughly explored in this context. The aim of the study is to determine the influence mechanisms between challenge-hindrance stressors and innovative performance among Chinese dental graduate students. The results of an innovation performance survey conducted with 822 dental graduate students from 13 public medical colleges show that there exists a significant association between challenge stressors and innovative performance, and a negative correlation is shown between hindrance stressors and innovative performance. Both types of stressors have indirect relationships with emotional exhaustion and learning engagement. Additionally, physical exercise moderates the indirect impacts of two stressors on innovative performance by emotional exhaustion and learning engagement. Overall, the findings suggest that increasing the frequency of physical exercise is an effective way to reduce stress and enhance innovation capacity. These results are useful in terms of raising students’ level of competition in the medical field.